234k views
5 votes
What is the solution to the equation 6Y -2(Y + 1) = 3(Y - 2) +6?

User Rebeca
by
5.4k points

2 Answers

2 votes

Answer:

6y-2(2y+1) = 3(y-2)+6

6y - 2y - 2 = 3y -6 + 6

add like terms:

4y - 2 =3y

4y - 3y = 2

y = 2

Explanation:

User Laurabeth
by
5.1k points
2 votes

Answer:

Y =2

Explanation:

6Y -2(Y + 1) = 3(Y - 2) +6

Distribute

6Y -2Y -2 = 3Y -6 +6

4Y -2 = 3Y

Subtract 4Y from each side

4Y - 4Y -2 = 3Y-4Y

-2 = -Y

Multiply each side by -1

2 = Y

User Rekna
by
5.3k points